ORGANIZATIONAL ASPECTS OF THE FORMATION OF CLINICAL STANDARDS FOR THE PREVENTION OF DENTAL DISEASES - Елена Александровна Тё; Игорь Анатольевич Тё; Елена Александровна Киселева; Динар Минзагитович Гарафутдинов; Маргарита Владимировна Сергеева; Сергей Владимирович Черненко; Ксения Сергеевна Киселева; Вадим Гельевич Мозес; Елена Владимировна Рудаева; Светлана Ивановна Елгина; Кира Борисовна Мозес; Яэль Центер (Медицина в Кузбассе, 2023)
The leading direction in the field of protection and strengthening of public health is the system of primary preventive measures, involving the identification and elimination of risk factors for the development of diseases. In the formed permanent bite in boys and girls of Kuzbass, a high prevalence of caries is determined (87.4 %) with an average intensity of damage to the CPU = 4, and 37.3 % of carious cavities are localized on the contact surfaces of teeth, the frequency of lesions with this localization has a direct correlation with the crowding of teeth. The prevalence (57 %) and intensity (of the affected sextants 1.0) of signs of periodontal tissue damage, which have a direct correlation with dental anomalies, through a change in microcirculation in the marginal periodontal. Morphometric characteristics of the dental system in the formed permanent bite in boys and girls of the Kemerovo region have regional characteristics, which requires the introduction of correction coefficients in the calculations. Regional features of anthropometric indicators of the dental apparatus are implemented as a way to improve the methods of diagnosis and prevention of dental diseases. Identification and study of risk factors is productive and for the purposes of secondary prevention of dental diseases, many risk factors for various forms of non-infectious pathology aggravate the course of the underlying disease, increase the likelihood of severe forms.